KHUSUSI METHOD IN ISLAMIC COMMUNICATION PERSPECTIVE (AN ANALYSIS OF THE DAKWAH MODEL OF THE JAMAAH TABLIGH IN LANGSA, ACEH) - Masdalifah Sembiring; Dedy Surya (ORASI: Jurnal Dakwah dan Komunikasi, 2023)
This study explains the particular dakwah model as a communication method carried out by the Jamaah Tabligh (JT). Some questions studied are how the model is specialized in the dakwah of JT and how this dakwah method is in the perspective of Islamic communication. By using qualitative methods, this study concludes that specialization is a program carried out by JT by visiting or visiting peoples homes. During the visit, messages will be communicated according to the person visited. There are five variants of the particular method. The systematic series of the unique method pays excellent attention to the communicant. This is in accordance with the ethical principles of Islamic communication, namely communication procedures that are in accordance with moral values by containing Islamic elements that direct humans to the benefit of the world and the hereafter in the form of human relationships with God (faith), fellow humans and the universe.